2013
DOI: 10.1016/j.jas.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Allochthonous red pigments used in burial practices at the Copper Age site of Valencina de la Concepción (Sevilla, Spain): characterisation and social dimension

Abstract: The use of red pigments linked to burial practices is widely documented in the Iberian prehistoric record and very often it has been traditionally interpreted as a ritual practice entailing the utilisation of local raw materials (iron oxides). Some research works, nevertheless, have also detected the use of red pigments which can only be interpreted as allochthonous. The red pigments spread over a single inhumation in a monumental Megalithic tomb surrounding Valencina de la Concepción Copper Age settlement was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 27 publications
0
28
0
2
Order By: Relevance
“…Emslie et al [209], report mercury poisoning probably associated with cultural use of cinnabar at the Neolithic site of Perdigões, near Evora in Portugal. Direct evidence comes from Rogerio-Candelera et al [210] who have excavated cinnabar, identified by Raman spectroscopy and XRD, in burial contexts from the Chalcolithic period (3rd Millenium BC) at Valencina de la Concepción, near Seville. The authors do not attempt to Provenance the source of cinnabar but Almadén, lying some 200 km to the NE is a likely source.…”
Section: Cinnabarmentioning
confidence: 99%
“…Emslie et al [209], report mercury poisoning probably associated with cultural use of cinnabar at the Neolithic site of Perdigões, near Evora in Portugal. Direct evidence comes from Rogerio-Candelera et al [210] who have excavated cinnabar, identified by Raman spectroscopy and XRD, in burial contexts from the Chalcolithic period (3rd Millenium BC) at Valencina de la Concepción, near Seville. The authors do not attempt to Provenance the source of cinnabar but Almadén, lying some 200 km to the NE is a likely source.…”
Section: Cinnabarmentioning
confidence: 99%
“…Pigments covering human bones were identified as hematite and magnetite. Rogerio‐Candelera et al investigated red pigments spread over a single inhumation in a monumental Megalithic tomb surrounding Valencina de la Concepción, a Copper Age settlement. Cinnabar, mixed with small amounts of iron oxides, was diffusely found; its provenance and use for funerary purposes are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Another discussion that is common in some studies is the pigment provenance (Jezequel et al 2011;Bonneau et al 2012;Domingo et al 2012;Rogerio-Candelera et al 2013). As the colourant minerals identified for Eireira and Leira das Mamas are very common in the region (Teixeira et al 1972;Pereira 1992), we can accept that these pigments were probably made using local materials.…”
Section: Discussionmentioning
confidence: 84%